Development of an ELISA for distinguishing convalescent sera with Mycoplasma hyopneumoniae infection from hyperimmune sera responses to bacterin vaccination in pigs. Issue 5 (22nd May 2021) - Ding, Honglei; Wen, Yukang; Xu, Zuobo; Zhou, Bingqian; Tlili, Chaker; Tian, Yaqin; Wang, Zhaodi; Ning, Yaru; Xin, Jiuqing
Abstract: Vaccination with inactivated bacterin is the most popular and practical measure to control enzootic pneumonia. After immunisation with inactivated bacterin, Mycoplasma hyopneumoniae colonised on the respiratory tract and lung stimulates the humoural immune responses and produces IgG and IgA antibodies. ELISA is a widely used serological method to detect M. hyopneumoniae antibodies. However, commercial IgG‐ELISA kit cannot distinguish between inactivated bacterin‐induced hyperimmune sera and convalescent sera stimulated by natural infection. SIgA‐ELISA method needs to collect nasal swabs, but collecting nasal swabs is not easy to operate. Establishment of a discriminative ELISA detecting humoural IgG from convalescent sera but not hyperimmune sera facilitates to evaluate the natural infection of M. hyopneumoniae after inactivated bacterin vaccination. We expressed and purified a recombinant protein named Mhp366‐N which contains an epitope recognised by the convalescent sera but not hyperimmune sera. The developed discriminative IgG‐ELISA could discriminate between inactivated bacterin‐induced hyperimmune sera and convalescent sera and was reproducible, sensitive and specific to M. hyopneumoniae antibody produced by natural infection. Compared to SIgA‐ELISA method, discriminative IgG‐ELISA was more convenient to detect IgG antibody from sera than IgA from nasal swabs, although it has limited sensitivity in the early stages of infection. Additionally, to some extent, it has a potential to avoid the interference of maternally derived IgG antibodies. The established discriminative IgG‐ELISA was efficient to judge the serological IgG antibodies induced from natural infection or inactivated vaccine stimulation and provided a useful method to investigate and evaluate the live organism infection after the application of inactivated bacterin. Abstract : An indirect IgG‐ELISA was developed to evaluate M. hyopneumoniae infection but not bacterin vaccination. The method was reproducible, sensitivity and specificity. This method was comparable to SIgA‐ELISA but more convenient.